Composição da carcaça e qualidade da carne de duas linhagens suínas comerciais - Reis, Serly Lourenço Borges (2011)
The objective was to compare two different lineages that have undergone genetic selections considering the quantitative characteristics of the carcass, intestinal morphology, intestinal absorption and quality of meat and see if these are correlated with the yield of lean meat. were studied 120 pigs, half barrows and half female, with approximately 150 days old on commercial farms, to compare two different genetic lineages: Lineage 1 - ½ (Large White and Pietran) x ½ (Large White and Landrace) and Lineage 2 - ½ (Large White, Pietran, Duroc and Hampshire) x ½ (Large White, Landrace, Meishan and Fengjing). In 60 animals of each genotype were analyzed the following characteristics: hot carcass weight (HCW), carcass length (CL), backfat thickness (BT), percentage thin meat ( CM%) , intramuscular fat (IMF) and intestinal length (CI). For the analysis of intestinal absorption (IA) of 62 animals were used only from those previously evaluated , and 31 animals of each genotype. The lineage 1 was called a "European" and the lineage 2 of "Chinese". The average values of CC and GIM differ between strains, and the European were higher. The meat of animals studied showed a low content of GIM, existing significant negative correlation between the CM and ET%. The strains showed IC, AI and CM% statistically equal.